Ultrasound diagnosis of placental and umbilical cord anomalies in singleton pregnancies resulting from in-vitro fertilization. (January 2023) - Larcher, L.; Jauniaux, E.; Lenzi, J.; Ragnedda, R.; Morano, D.; Valeriani, M.; Michelli, G.; Farina, A.; Contro, E.
Abstract: Introduction: placental anomalies can affect fetal and maternal outcome due to severe maternal hemorrhage potentially resulting in hysterectomy and cord accident including abruption that can determine fetal damage or death. The aims of our study are to determine if the rate of placental and umbilical cord anomalies are more common in IVF singleton pregnancies compared to spontaneous pregnancies; to evaluate the role of ultrasound in screening for these anomalies and to investigate if oocyte donor fertilization is an additional risk factor for the development of these anomalies. Methods: this was a prospective cohort study involving two tertiary centers. Patients with a singleton pregnancy conceived with IVF and patients presenting with a spontaneous conception were recruited between 1 st May 2019 to 31 st March 2021. A total of 634 pregnancies were enrolled in the study. All patients underwent similar antenatal care, which included ultrasound examinations at 11–14, 19–22 and 33–35 weeks. Ultrasound findings of placental and/or umbilical cord abnormalities were recorded using the same protocol for both groups and confirmed after birth. Results: IVF pregnancies had a significantly higher risk of low-lying placenta, placenta previa, bilobed placenta and velamentous cord insertion (VCI) compared with spontaneous pregnancies. In the heterologous subgroup there was a significant increased incidence of placenta accreta spectrum (PAS) disorders than in spontaneous pregnancies. All these anomalies were identified prenatally on ultrasound imaging and confirmed at birth. Discussion: IVF pregnancies in general and those resulting from donor oocyte in particular are at higher risk of placental and umbilical cord abnormalities compared to spontaneous pregnancies. These anomalies can be diagnosed accurately at the mid-trimester detailed fetal anomaly scan and our findings support the need for a targeted ultrasound screening of these anomalies in IVF pregnancies. Highlights: IVF pregnancies are at higher risk of placental abnormalities compared to spontaneous. Heterologous IVF pregnancies are at higher risk of placenta accreta spectrum. US has a high diagnostic accuracy in detecting placental anomalies prenatally.